(untitled) (Journal of Pharmaceutical Negative Results, 2010)
Objective: The effect of petroleum ether extract of Bauhinia racemosa was investigatedin rats and mice to evaluate the analgesic activity. Materials and Methods: Acetic acidinduced writhing model and hot plate method were employed to test the analgesicactivity. Results: The results indicated that the petroleum ether extract had nosignificant analgesic activity. Conclusion: It may be inferred that Bauhinia racemosa donot have analgesic activity and the results are not in agreement with its traditional use.